Epidemic situation of cestodiasis in domestic reindeer on reindeer farms in the Murmansk Oblast - R. A. Pochepko; A. P. Kartashova; A. Lavikainen; S. Malkamäki (Ветеринария сегодня)
The paper presents the results of the cestodiasis epidemic situation in domestic reindeer in the farms of the Murmansk Oblast. The studies were performed in 2018–2019 during the routine slaughter of reindeer at slaughter houses APC “Tundra” and APC HFE SEN “Olenevod” located in settlements Lovozero, Krasnoschelye, and Sosnovka. Totally 4,048 carcasses of domestic reindeer were tested, 2,812 out of them – in Lovozero, 396 – in Sosnovka, and 840 – in Krasnoschelye. During the meat inspection the parenchymal organs were examined for cestode cysts. When detected they were sampled and gross specimens were prepared using standard parasitological methods. 56 samples of internal organs of deer suspected in tapeworm infestation were collected from the inspected carcasses, in 25 of them tapeworms were detected and in the rest of the samples parasites were not detected. The tapeworm species were determined at the Department of Veterinary Biosiences, Faculty of Veterinary Medicine, University of Helsinki. The test performed revealed echinococcosis (Echinococcus canadensis) and cysticercosis (Taenia hydatigena). Most lesions were detected in liver where the agent’s larvae cysts are observed. It was established that the level of domestic reindeer infestation with the agents of cysticercosis in APC “Tundra” was 0.5%, echinococcosis – 0.04%, in APC HFE SEN “Olenevod” cysticercosis was diagnosed in 0.81% cases, echinococcosis was not detected. On the whole 0.62% of reindeer on reindeer farms were infested with cestodes. Measures taken for prevention of helminth infestation in domestic and farm animals bear good results.